2019
DOI: 10.32604/phyton.2019.04784
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Application Improves the Drought Tolerance in Maize Seedlings

Abstract: Application of biochar to agricultural soils is mostly used to improve soil fertility. Experimental treatments were comprised of two factors: i) drought at two level, i.e., 80% and 40% water holding capacity (WHC) which was maintained on gravimetric basis ii) three levels of biochar i.e., control, 2 t ha -1 and 4 t ha -1 added to soil. Experimentation was done to examine potential of biochar application to enhance the growth attributes, water relations, photosynthetic pigments and antioxidants activities in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
3
2
0
Order By: Relevance
“…Catalase was significantly lowered as compared to control in all drought treatments however with the addition of biochar and PGPR the enzymatic activities were reported higher. Our results are linked to the findings of Abideen et al (2020), Sattar et al (2019), and Abbas et al (2018) who stated that application of growth promoters alleviated the negative affect of water deficit stress on antioxidant enzymes and enhanced the enzymes activities.…”
Section: Discussionsupporting
confidence: 90%
“…Catalase was significantly lowered as compared to control in all drought treatments however with the addition of biochar and PGPR the enzymatic activities were reported higher. Our results are linked to the findings of Abideen et al (2020), Sattar et al (2019), and Abbas et al (2018) who stated that application of growth promoters alleviated the negative affect of water deficit stress on antioxidant enzymes and enhanced the enzymes activities.…”
Section: Discussionsupporting
confidence: 90%
“…Salty water induced a significant increase in antioxidant enzymatic activity (SOD, CAT and APX), lipid peroxidation (MDA), and membrane injury index (MII) with a defense mechanism against the detrimental effects of salinity. Similar results were obtained in the studies conducted by Gharib et al (2016) and Sattar et al (2019). ROS production leads to oxidative damage (protein degradation, membrane damage, esc.…”
Section: Resultssupporting
confidence: 88%
“…There was also detected a significant decrease in a/b in both 2.5% and 7.5% BC (Z) treatments compared to the control, but we attribute this feature to the overall inhibited synthesis of chlorophyll in these treatments. Similarly, to our findings, the study of Sattar et al, [92] revealed that biochar application increased contents of photosynthetic pigments-chlorophyll a, b, a + b and a/b ratio in maize (Zea mays L.) seedlings and it was concluded that biochar application is an efficient way to mitigate adverse effect of drought stress [92].…”
Section: Plant Biomass and Its Quality Parameters-chlorophylls And Ca...supporting
confidence: 89%